PENGARUH KERJASAMA GURU DAN ORANG TUA TERHADAP PEMBENTUKAN KARAKTER KEDISIPLINAN PESERTA DIDIK DI SDN 3 CEMPAKA - HARTATI HARTATI (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
The purpose of this study was to determine the effect of the collaboration between teachers and parents on the formation of disciplinary character of students using quantitative descriptive methods, the tools used in extracting the main data were questionnaires. From the results of statistical analysis pay attention to the significant level (ɑ) 5% and df (degrees of freedom) = the amount of data - 2 or 30-2 = 28, so that the t table is 1.701 at the 5% significant level. Thus, tcount = 80.9> ttable = 1.701, meaning that Ha which says